Seed quality as affected by intercropping of Chickpea and L. iberica - Maryam Mirdoraghi; Saeideh Maleki Farahani; Alireza Rezazadeh (PLoS ONE, 2025)
Producing high-quality seeds is a significant priority for the agricultural industry and plays a vital role in enhancing and stabilizing crop yields. However, the conditions experienced by a mother plant during seed development and maturation can significantly influence seed quality. Intercropping oilseeds with other crops, especially legumes, may contribute to a sustainable food supply and increase agricultural sustainability and resilience. Therefore, the objective of this research was to investigate the effect of intercropping on the quality of seeds from dragon’s head ( Lallemantia iberica ) and chickpea ( Cicer arietinum ) produced under different irrigation regimes and sowing dates. Seeds of chickpea and L. iberica were obtained from the research farm of the Agricultural College of Shahed University in Tehran, Iran, where the maternal plants were grown under: a) three irrigation regimes (irrigation after 20% (I 20 : short interval), 40% (I 40 : medium interval) of soil available water depletion, and supplementary irrigation (IS: long interval) in only two stages, including the sowing and pre-flowering stages, based on a 20% depletion of soil available water); b) the autumn sowing date on November 6 (S 1 ) and the spring sowing date on March 6 (S 2 ); and c) sole system and intercropping treatments included: a) sole system (Ss), and b) intercropping of 50% chickpea: 50% L. iberica (Ic), applied across two consecutive years, 2021–22 and 2022–23. This study found that Ic (I 20 S 1 ) and Ic (I 40 S 1 ) treatments improved germination indexs due to favorable maternal plant conditions. In contrast, Ic (I S S 2 ) and Ic (I S S 1 ) treatments increased stress markers such as hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), and electrical conductivity (EC). Intercropping also enhanced seed nutrient content ((nitrogen (N), phosphorus (P), potassium (K)) and fatty acid levels, which correlated positively with germination indexs. These findings suggest that intercropping systems, especially Ic (I 20 S 1 ) and Ic (I 40 S 1 ) treatments, are an effective strategy for improving seed quality, resilience to water stress, and agricultural sustainability.